2022
DOI: 10.3991/ijoe.v18i14.34435
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Networks on Assembling Classification Models to Detect Melanoma Skin Cancer

Abstract: In 2020, there were more than 1.2 million new skin cancer diagnoses, and melanoma was the most recurrent type of cancer. On the other hand, melanoma is the least common but most serious form of skin cancer affecting both men and women. This work aims to assemble classification models to detect a case of melanoma with high accuracy based on a Convolutional Neural Networks system. The methodology considers training 21 models for image classification, with the best assembly performance of  EfficientNet and VGG-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…Medical imaging analysis plays a critical role in diagnosing disease such as diabetic retinopathy [19], skin cancer [20] and lung disease [21]. In literature, several studies have been reported for automatic segmentation of myocardial scar and edema.…”
Section: Related Workmentioning
confidence: 99%
“…Medical imaging analysis plays a critical role in diagnosing disease such as diabetic retinopathy [19], skin cancer [20] and lung disease [21]. In literature, several studies have been reported for automatic segmentation of myocardial scar and edema.…”
Section: Related Workmentioning
confidence: 99%
“…Among such processes, the RRP aims to review incoming requests, validate data and business rules, register data through technological tools and register requests to proceed to their referral through the corresponding channel. Intelligent Processes are also considered those systems that, from the processing of data and images, can detect behavioral patterns or trends [17][18][19][20][21][22][23].…”
Section: Business Processmentioning
confidence: 99%
“…This approach, however, is constrained by its inability to ensure continuous monitoring. The advent of Internet of Things (IoT) and Digital Image Processing (DIP) technologies has demonstrated their efficacy, as they find application in various domains to support, facilitate, and resolve diverse challenges [17], [18], [19], [20], [21].…”
Section: Introductionmentioning
confidence: 99%